Nicolau Syndrome: A Review of Case Studies - Paria Mojarrad; Hamid Mollazadeh; Behnaz Barikbin; Mohammad Bagher Oghazian (Tabriz University of Medical Sciences, 2022)
Nicolau syndrome, although it is quite rare, often occurs following intramuscular injections of different medications, especially diclofenac and penicillins. Accordingly, its symptoms usually begin with severe pain during injection, leading to ulceration and necrosis of the local tissue over time. Immediate diagnosis and treatment in the case of this syndrome, are of great importance. There are no established criteria for Nicolau's diagnosis, and preferably, these can be achieved by examining the patient's symptoms and eliminating differential diagnoses. The proposed treatments are primarily symptomatic therapy and measures such as fasciotomy, debridement, and plastic surgery provided in the affected area. The exact cause of this syndrome has not been determined yet. However, since vasospasm, thrombosis, and embolism have been observed in most of Nicolau syndrome cases, so any intra-arterial/para-arterial injection or any other factor leading to these three conditions could be hypothetically regarded as the cause of this problem. This review aims to provide a comprehensive overview of Nicolau's symptoms, diagnosis, treatment methods, and prevention. It also investigates the association between the incidence of this disease and some factors such as gender, age, injection method, and causative drugs, in order to widen our understanding on this syndrome and help practitioners with a much faster diagnosis method and step-by-step approach to Nicolau syndrome.